Blockage of ERCC6 Alleviates Spinal Cord Injury Through Weakening Apoptosis, Inflammation, Senescence, and Oxidative Stress - Zou, Peng; Zhang, Xiaoping; Zhang, Rui; Chai, Xin; Zhao, Yuanting; Li, Erliang; Zhang, Qian; Yan, Rongbao; Yang, Junsong; Liao, Bo (Frontiers in Molecular Biosciences, 2022)
Objective: Spinal cord injury (SCI) is a devastating disease resulting in lifelong disability, but the molecular mechanism remains unclear. Our study was designed to observe the role of excision repair cross-complementing group 6 (ERCC6) following SCI and to determine the underlying mechanism. Methods: SCI mouse models and LPS-induced microglia cell models were established. ERCC6 expression was blocked by ERCC6-siRNA-carrying lentivirus. Nissl staining was utilized for detecting neuronal damage, and apoptosis was analyzed with TUNEL and Western blotting (apoptotic markers). Immunofluorescence was used for measuring macrophage markers (CD68 and F4/80) and astrocyte and microglia markers (GFAP and Iba-1). Pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) were measured via ELISA. Senescent cells were estimated via SA-β-Gal staining as well as Western blot (senescent markers p21 and p27). Oxidative stress was investigated by detecting the expression of 4-HNE, Nrf2, and Keap1, and intracellular ROS levels. Results: ERCC6 expression was remarkably upregulated both in the spinal cord of SCI mice and LPS-induced microglia cells. ERCC6 deficiency alleviated neuronal damage and apoptosis. Macrophage infiltration and inflammatory response were suppressed by si-ERCC6 treatment. Moreover, ERCC6 blockage ameliorated astrocyte and microglia activation and cell senescence in the damaged spinal cord. Excessive oxidative stress was significantly decreased by ERCC6 knockdown in SCI. Conclusion: Collectively, ERCC6 exerts crucial functions in mediating physiological processes (apoptosis, inflammation, senescence, and oxidative stress), implying that ERCC6 might act as a prospective therapeutic target against SCI.